2013
DOI: 10.1542/peds.2012-3344
|View full text |Cite
|
Sign up to set email alerts
|

Severe Early-Onset Colitis Revealing Mevalonate Kinase Deficiency

Abstract: Hyperimmunoglobulinemia D is the less severe form of mevalonate kinase deficiency (MKD) caused by recessive inherited mutation in the mevalonate kinase gene. Hyperimmunoglobulinemia D is characterized by febrile attacks, often associated with transient digestive manifestations, such as abdominal pain, diarrhea, and vomiting. Here we report for the first time 2 patients with MKD revealed by severe neonatal colitis. Both patients had chronic bloody diarrhea and failure to thrive; 1 patient since the age of 1 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 14 publications
(15 reference statements)
1
37
0
1
Order By: Relevance
“…To assess the effects of thiopurine treatment, some CD patients were recruited immediately prior to commencing AZA therapy, and longitudinal blood sampling was conducted over a followup period of 6 months. The analyses of Vδ2 T cell subset distribution in peripheral blood were conducted in a subgroup of pediatric CD patients (mean age, 13 years [range [7][8][9][10][11][12][13][14][15][16][17][18][19]; 50% male; CRP, mean 12.5 mg/l [range 5-39 mg/l]) and sex/age/ethnicity-matched IBS controls (mean age, 13 years [range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; 50% male; CRP, <5 mg/l) in order to limit the effects of demography, historical pathogen exposure, and concomitant therapies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effects of thiopurine treatment, some CD patients were recruited immediately prior to commencing AZA therapy, and longitudinal blood sampling was conducted over a followup period of 6 months. The analyses of Vδ2 T cell subset distribution in peripheral blood were conducted in a subgroup of pediatric CD patients (mean age, 13 years [range [7][8][9][10][11][12][13][14][15][16][17][18][19]; 50% male; CRP, mean 12.5 mg/l [range 5-39 mg/l]) and sex/age/ethnicity-matched IBS controls (mean age, 13 years [range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; 50% male; CRP, <5 mg/l) in order to limit the effects of demography, historical pathogen exposure, and concomitant therapies.…”
Section: Methodsmentioning
confidence: 99%
“…PAg are produced by a wide range of bacteria that can colonize the gut (1) and can also accumulate in host cells due to dysregulation of the mevalonate kinase metabolic pathway during malignant transformation or microbial infection (5,6). Intriguingly, human patients with mutations in the mevalonate kinase gene exhibit a severe neonatal colitis that can be successfully treated with bisphosphonate drugs, which modulate PAg synthesis and alter Vδ2 T cell function in vivo (7)(8)(9)(10). We recently reported that PAg exposure stimulates human blood Vδ2 T cells to upregulate the gut-homing integrin α4β7, and we identified Vδ2 T cells in human colonic biopsies that produced proinflammatory cytokines and enhanced IFNγ synthesis by intestinal CD4 + T cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, abdominal symptoms may arise from potentially lifethreatening complications of HIDS, such as the bowel strangulation with subsequent necrosis that occurred in one of our patients. Severe inflammatory colitis has been reported in two neonates as the presenting feature of HIDS [27]. Moreover, genetic variants associated with inflammatory bowel disease were recently found in a series of MKD patients [3].…”
Section: Commentsmentioning
confidence: 93%
“…These include the anti-tumor necrosis factor alpha (TNFα) agents infliximab [24,27], etanercept [53,54], and adalimumab [15], the anti-interleukin (IL)-1 agents anakinra [5,7,15,27] and canakinumab [15], and the IL-6 antagonist tocilizumab [41].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we wish to focus the attention on six patients suffering from mevalonate kinase deficiency (MKD, OMIM #260920), diagnosed during the first year of life and followed-up at the Institute for Maternal and Child Health—IRCCS ‘Burlo Garofolo’ (Trieste, Italy). MKD, caused by inherited recessive mutations in the mevalonate kinase gene ( MVK ), is characterised by febrile attacks, often associated with abdominal pain, diarrhoea and vomiting; it can be considered as an auto-inflammatory defect predisposing to IBD-like intestinal inflammation 3 4. The six MKD patients were homozygous and/or heterozygous for missense mutations on the MVK gene (table 1).…”
mentioning
confidence: 99%